MogR Is a Ubiquitous Transcriptional Repressor Affecting Motility, Biofilm Formation and Virulence in Bacillus thuringiensis - Smith, Veronika; Josefsen, Malin; Lindbäck, Toril; Hegna, Ida K.; Finke, Sarah; Tourasse, Nicolas J.; Nielsen-LeRoux, Christina; Økstad, Ole Andreas; Fagerlund, Annette (Frontiers in Microbiology, 2020)
Flagellar motility is considered an important virulence factor in different pathogenic bacteria. In Listeria monocytogenes the transcriptional repressor MogR regulates motility in a temperature-dependent manner, directly repressing flagellar- and chemotaxis genes. The only other bacteria known to carry a mogR homolog are members of the Bacillus cereus group, which includes motile species such as B. cereus and Bacillus thuringiensis as well as the non-motile species Bacillus anthracis, Bacillus mycoides and Bacillus pseudomycoides. Furthermore, the main motility locus in B. cereus group bacteria, carrying the genes for flagellar synthesis, appears to be more closely related to L. monocytogenes than to Bacillus subtilis, which belongs to a separate phylogenetic group of Bacilli and does not carry a mogR ortholog. Here, we show that in B. thuringiensis, MogR overexpression results in non-motile cells devoid of flagella. Global gene expression profiling showed that 110 genes were differentially regulated by MogR overexpression, including flagellar motility genes, but also genes associated with virulence, stress response and biofilm lifestyle. Accordingly, phenotypic assays showed that MogR also affects cytotoxicity and biofilm formation in B. thuringiensis. Overexpression of a MogR variant mutated in two amino acids within the putative DNA binding domain restored phenotypes to those of an empty vector control. In accordance, introduction of these mutations resulted in complete loss in MogR binding to its candidate flagellar locus target site in vitro. In contrast to L. monocytogenes, MogR appears to be regulated in a growth-phase dependent and temperature-independent manner in B. thuringiensis 407. Interestingly, mogR was found to be conserved also in non-motile B. cereus group species such as B. mycoides and B. pseudomycoides, which both carry major gene deletions in the flagellar motility locus and where in B. pseudomycoides mogR is the only gene retained. Furthermore, mogR is expressed in non-motile B. anthracis. Altogether this provides indications of an expanded set of functions for MogR in B. cereus group species, beyond motility regulation. In conclusion, MogR constitutes a novel B. thuringiensis pleiotropic transcriptional regulator, acting as a repressor of motility genes, and affecting the expression of a variety of additional genes involved in biofilm formation and virulence.